Study of Flakes from Protein-Rich Flour and Essential Oils For Stunting Sufferers - Dedin Finatsiyatull Rosida; Sri Winarti; Nurul Firdausy (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The results of the Indonesian Nutrition Status Study (SSGI) in 2021, conducted by the Ministry of Health, the stunting rate in Indonesia in 2021 was 24.4 percent or decreased by 3.3 percent compared to 2019 (27.7 percent). However, when compared to countries in the ASEAN region, the prevalence of stunting in Indonesia is still higher than Vietnam (23%), Malaysia (17%), Thailand (16%) and Singapore (4%), only better than Myanmar (35%). Currently, Indonesia is experiencing what is called the triple burden of malnutrition. The triple burden of malnutrition is not just a matter of malnutrition, but also excess, and imbalance in nutritional intake. For this reason, snacks are made in the form of healthy flakes which can be used as an alternative to overcome the stunting problem in Indonesia. The purpose of this research is to produce healthy flake products rich in nutrients for stunting sufferers. The experimental design in this study consisted of two factors. The first factor was the proportion of corn flour: cowpea flour (50:50 ; 60:40 ; 70:30) and the second factor was the addition of 4% sunflower seed oil respectively. The result showed that the flake aproximately has 2,46-2,88% moisture content, 1,46-1,76% ash content, 3,76-5,91% fat content, 6,87-7,24% protein content, and 81,4-84,85% carbohydrate content.